THE MOVING FORWARD OF DIGITAL ISLAMIC FINANCIAL EDUCATION IN MALAYSIA: A CONCEPTUAL PAPER - Muhammad Zikry Hishamudin; Nur Shuhada Kamarudin; Noradilah Abdul Hadi (Journal of Islamic, Social, Economics and Development, 2023)
A critical review of the intention to use a digital platform for Islamic finance education reveals a lack of a conceptual framework. A conceptual framework is important for understanding the sustainable development of digital platforms for Islamic financial education. The current financial system's complexity makes it necessary to focus on developing financial education in Malaysia. Using a digital platform for Islamic financial education can make learning easier and more effective. This research will investigate the contributing factors from the Unified Theory of Acceptance and Use of Technology (UTAUT), such as social influence, effort expectancy, and performance expectancy, to the intention to use digital platforms for Islamic financial education. The conceptual framework has been developed to explain the research objective.